Optical and structural properties of Mn2+ doped PbGeO3-SbPO4 glasses and glass-ceramics - Volpi, V.; Montesso, M. [UNESP]; Ribeiro, S. J. L. [UNESP]; Viali, W. R.; Magon, C. J.; Silva, I. D. A.; Donoso, J. P.; Nalin, M. [UNESP] (Elsevier B.V., 2016)
This paper shows the study of optical and structural properties of SbPO4-PbGeO3-MnCl2 glass and glass-ceramics. Glass was prepared by melting-quenching methodology while the glass ceramic was obtained by controlled thermal treatment of the glass. The UV-Vis results show that the glass presents only Mn2+ species, but, the thermal treatment leads to oxidation of Mn2+ to Mn3+ species, what was evidenced by an absorption band in the visible range. High resolution transmission electron microscopy shows the presence of nanocrystalline phases of Mn2O3 and PbGeO3 confirming the formation of a glass-ceramic Electron paramagnetic resonance measurements suggest that manganese ions occupy only one environment in the glass. On the other hand, for glass-ceramic at least three different structural sites were identified by simulation of the EPR signal. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Glass; Glass-ceramic; Manganese; UV-Vis; EPR